A solution for flexible adaption of network services in mobile edge computing - Bohao FENG; Huachun ZHOU (Dianxin kexue)
In order to cope with the challenges brought by the “internet of everything”,mobile edge computing has been highly valued by academics and industry for its unique advantages.However,traditional IP networks are unable to provide network services dynamically in an efficient way for mobile edge computing,due to deficiencies from their original design.To this end,based on emerging network technologies,a solution for flexible adaptation of network services in mobile edge computing scenarios was proposed,aiming at realizing on-demand and effective deployment of network services to meet the diversified and personalized needs of different users.